The analysis of the last shots of the top-level tennis players in open tennis tournaments - Bulut Turhan; İbrahim Cam; Zeynep Onag (Selcuk University, 2014)
The aims of this study is to investigate the technical strokes and the last win and lost strokes, and contribute to prepare suitable technical training programs for the desired goal. In accordance with this purpose it has been monitored the semi and quarter final matches of the elite level tennis players Nadal, Federer, Agossi, Hewitt, Coria, Davydenko, Ljubcic and Ferrero in the U.S.A., Australia, Dubai, Doha and China 2005 Open Tennis Tournaments.  Video records of tennis matches in Eurosport Channel are later transferred in computer. Images in the computer are converted into an observation form by a notation method. Obtained data are transferred into Excel Program as shoot types, win or lose last shoots. Percentage distributions of the data are presented in tables. In our study 528 serving 1939 shoot technics are analyzed. The average rally durations are 3.7. 'The forehand technique' has been the most widely used (30.78%) and the best one to get scores (37.8%) of all. And 'the backhand technique' has been the worst one (48.7%).